Electrochemical Behaviour of Silica Deposited on Stainless Steel by Electrophoretic Deposition - Ni Made Intan Putri Suari; Delyana Ratnasari; Sahara Tulaini; W. Widiyastuti; Heru Setyawan (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
The purpose of this paper is to evaluate the characteristics of corrosion protection of stainless steel substrates coated with silica by electrophoresis with pulsed direct current (PDC) and constant direct current (CDC) with anodization. Electrophoresis was carried out using silica sol from sodium silicate solution as an electrolyte solution. Stainless steel functioned as an anode and carbon as a cathode with a constant electrode distance of 2 cm. The amplitude, duty cycle, and anodization effect on stainless steel corrosion protection characteristics were evaluated. The samples were characterized by linear polarization and electrochemical impedance spectroscopy (EIS) to see the characteristics of metal corrosion protection and scanning electron microscopy (SEM) analysis to see the morphology of the coating. This study showed that PDC electrophoresis and CDC accompanied by anodization could obtain silica film with good corrosion protection characteristics (high pore resistance and low admittance). Linear polarization results showed that metal corrosion protection behavior was increased by anodization. Similar results were obtained by EIS analysis which showed that pore resistance increased by anodization. The highest pore resistance obtained by the constant current with anodization is 543 ohms, and the lowest admittance is 0.0217. Corrosion protection characteristics are also influenced by the amplitude and duty cycle during electrophoresis. Silica film with a high pore resistance and a low admittance were obtained at a frequency, amplitude, and duty cycle of 80 Hz, 0.5 volts, and 60%, respectively. The silica film produced by pulsed electrophoresis resulted in better coating characteristics than by constant current with anodization, which is seen from the pore resistance value and its admittance.